The Lukan Beatitudes (Luke 6.20–26) in the Canonical Choir: A ‘Test Case’ for John Christopher Thomas’ Hermeneutical Proposal - Coleman, Rachel L. (Journal of pentecostal theology, 2017)
John Christopher Thomas proposes the metaphor of a black gospel choir as a hermeneutical tool that will allow interpreters to hear the diverse voices of Scripture in both their solo melodies and their joined harmonies. This paper uses an analysis of Luke’s beatitudes and woes as a test case for Thomas’ metaphor.